Fleksibilitas Keuangan melalui Manajemen Modal Kerja pada Perusahaan Manufaktur dalam Kondisi Ketidakpastian - Purwanto Purwanto (ITB AAS INDONESIA, 2021)
Changes in the business environment are increasingly dynamic, uncertain and unpredictable. Financial flexibility through working capital management is important for either a survival strategy, adaptive or proactive in taking advantage of opportunities for change. This study aims to examine and analyze the effect of working capital management on company profitability under uncertainty. The research design was carried out in a natural laboratory during the uncertainty period of the 2008 global financial crisis. The study was conducted by comparing working capital management and performance of 106 manufacturing companies based on data from the Indonesia Capital Market Directory around the crisis period (2007-2011). Data analysis used multiple linear regression. The effect of the financial crisis is analyzed through simulation analysis. The results of the study found that the more conservative working capital policy for investment has a positive effect on profitability performance, while the greater the short-term liabilities become an obstacle to profitability performance. However, the effect of working capital policies for financing changed during the crisis period. The proportion of working capital to finance short-term debt has a positive effect on profitability performance in crisis conditions. The results of this study have implications for the role of working capital policies for financial flexibility under conditions of crisis and uncertainty. Keywords: Financial Flexibility, Working Capital, Uncertainty